Psychosocial determinants of breastfeeding behavior in Songkhla Province, Thailand - Permsiri Nitimanop (1986)
This study investigated the psycho-social determinants of breastfeeding behavior with the hypothesis that there is no association between breastfeeding behavior (the dependent variable) and the independent varibles, namely: behavior intentions, social support, accessibility of health services, personal autonomy and aspiration, socio-demographic characteristics, and knowledge and attitude toward breastfeeding. The study was conducted in Songkhla province, using the survey method with an interview schedule as the basic instrument in collecting data. 2-stage stratified cluster sampling was used. 712 mothers in their last trimester of pregnancy were included in the study for the initial interview. 630 were included in the final interview 4 to 6 weeks after delivery. 78 dropped out while 4 cases could not be included because their babies died. Mothers were categorized into those who completely breastfed (CBF) and those who mixed-fed (MF). The X2-test was used to investigate the association between the type of infant feeding, i.e. CBF vs. MF and each independent variables. The prediction behavior model was determined by using logistic multiple regression under SAS program. The study revealed that CBF behavior was associated with place of residence, spouses' education, working status, family income, wanted pregnancy, intention to breastfeed, intention to suggest breastfeeding to duaghters and friends, satisfaction with health services, the past levels of striving, the education aspiration for daughters, information about breastfeeding, and specific knowledge and attitude toward breastfeeding. The 4 main variables found to be significant predictors in the behavior model were behavior intention (intention to breastfeed and intention to suggest breastfeeding to daughters), satisfaction with health services (both high and middle levels), information about breastfeeding and place of residence. For cost benefit purposes, policy makers and program planners should consider these factors when planning BF promoting programs. If the above determinants were present in a given program it can be predicted that 8-9 out of 10 mothers would completely breadfeed their babies in Songkhla province.
Thesis (DrPH Health Education)--University of the Philippines, Manila
Keywords: Breast feeding -- Thailand